Audit Opinion and Company Size on Earning Management as moderated by the Audit Committee at Sharia Commercial Banks in Indonesia - Chairunisa, Mariyam (Countable (Contemporary Business and Sustainability Science), 2024)
This research examines the influence of audit opinion and company size on earnings management moderated by the audit committee at Islamic commercial banks in Indonesia in the period 2017 - 2022. There are many reasons why management carries out earnings management, including conflicts of interest that occur between management as agents and investors as principals, which often benefits one party. Earnings management practices can affect the fairness of the presentation of financial reports, so that financial reports can mislead users even though they should be useful for the users. The research method used is a saturated sample method which uses secondary data in the form of annual reports from fifteen Islamic commercial banks in Indonesia which provide Annual Reports. The data obtained was processed with moderate regression analysis (MRA) using SPSS statistical tools. The results of this research state that audit opinion has no effect on earnings management, but on the contrary, company size has an effect on earnings management. Furthermore, the audit committee is unable to moderate both audit opinion and company size on earnings management. It is hoped that this research can become a reference for further research.